Bacteria‐induced production of the antibacterial sesquiterpene lagopodin B in Coprinopsis cinerea. Issue 2 (29th May 2019) - Stöckli, Martina; Morinaka, Brandon I.; Lackner, Gerald; Kombrink, Anja; Sieber, Ramon; Margot, Céline; Stanley, Claire E.; deMello, Andrew J.; Piel, Jörn; Künzler, Markus
Summary: Fungi defend their ecological niche against antagonists by producing antibiosis molecules. Some of these molecules are only produced upon confrontation with the antagonist. The basidiomycete Coprinopsis cinerea induces the expression of the sesquiterpene synthase‐encoding gene cop6 and its two neighboring genes coding for cytochrome P450 monooxygenases in response to bacteria. We further investigated this regulation of cop6 and examined if the gene product is involved in the production of antibacterials. Cell‐free supernatants of axenic cultures of the Gram‐positive bacterium Bacillus subtilis were sufficient to induce cop6 transcription assessed using a fluorescent reporter strain. Use of this strain in a microfluidic device revealed that the cop6 gene was induced in all hyphae directly exposed to the supernatant and that induction occurred within less than one hour. Targeted replacement of the cop6 gene demonstrated the requirement of the encoded synthase for the biosynthesis of the sesquiterpene lagopodin B, a previously reported antibacterial compound from related species. Accordingly, lagopodin B from C. cinerea inhibited the growth of several Gram‐positive bacteria including B. subtilis but not Gram‐negative bacteria. Our results demonstrate that the C. cinerea vegetative mycelium responds to soluble compounds of a bacterial culture supernatant by local production of an antibacterial secondary metabolite. Abstract : The production of secondary metabolites by microorganisms is often tightly regulated. Here, we show that the production of an antibacterial sesquiterpene by the vegetative mycelium of the mushroom Coprinopsis cinerea is induced by soluble compounds from supernatants of axenic cultures of the bacterium Bacillus subtilis . This finding implies that representatives of the fungal phylum Basidiomycota are able to sense the presence of bacterial antagonists in their environment and to mount a respective defense response.